2011
DOI: 10.3928/01484834-20110317-03
|View full text |Cite
|
Sign up to set email alerts
|

Success in Nursing School: Black Nursing Students’ Perception of Peers, Family, and Faculty

Abstract: Blacks comprise 12.3% of the U.S. population and only 4.6% of registered nurses nationally. Moreover, Blacks have the highest percentage of nongraduates among nursing students compared with other U.S. racial/ethnic groups. This descriptive qualitative study examined the perceptions and experiences that contributed to success for Black graduates, ages 18 to 50, who attended nursing degree programs with predominantly White students and identified the experiences students credited for their success. Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…This will ultimately aid in developing new strategies to increase the number of minority students in the nursing profession [8,22] .…”
Section: Discussionmentioning
confidence: 99%
“…This will ultimately aid in developing new strategies to increase the number of minority students in the nursing profession [8,22] .…”
Section: Discussionmentioning
confidence: 99%
“…The predictive power of supportive supervision was significant only in females (β=0.19). On the other hand, in previous research, support from staff and family, which was similar concept to supportive supervision of this study, was found to be important for non-traditional students and minorities [15][16][17][18]. Considering that the zero-correlations between supportive supervision and major satisfaction were significant in both genders (males, r=0.32, females, r=0.39), it is not reasonable to conclude that supportive supervision was not associated with major satisfaction.…”
Section: Discussionmentioning
confidence: 76%
“…Secondly, we also considered social support as one of the social or educational predictors that might affect satisfaction with the nursing major. This is based on previous research showing that social support from, and communication with, colleagues has a positive impact on satisfaction in the nursing profession [15,16]; social support from faculty members also has a marked effect on retention [17]; and social support promotes retention in Afro-American and male nursing students, who are minority groups in nursing schools [18]. However, social support is a general element not limited in its effect to majors and other academic activities.…”
Section: Introductionmentioning
confidence: 99%
“…(AACN, 2011) A more diverse nursing workforce increases health care access and quality in ethnically diverse populations [8,19,21] . Increasing diversity in the healing professions is one way The Sullivan Commission (2004) has identified will bring about changes in health disparities by having providers who are culturally similar to and sensitive to patients in healthcare's medically underserved communities [2,6,21] . In 2008, a partnership between the Robert Wood Johnson Foundation (RWJF) and Institute of Medicine (IOM) was forged with the purpose of making recommendations for transforming the future of nursing and the way Americans receive health care.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature there are several studies citing perceptions of what minority nursing students stated helped them succeed and remain in nursing programs [5][6][7][8][9] . Moreover, Noone [11] published a literature review that described strategies that were used in nursing education between 2002 and 2007 to recruit, retain, and graduate more minorities.…”
Section: Introductionmentioning
confidence: 99%